Influence of Country-of-Origin Reputation Towards Attitude and Intention to Adopt Chinese Electric Vehicle in Indonesia - Aristanty, Maria Audrey; Wijaya, Grace; Mustikasari, Faranita (Dinasti Publisher, 2025)
This study aims to identify the factors that influence the adoption of Chinese electric vehicles in Indonesia. To achieve this, it employs a modified theory of planned behavior. The study initially examines how China’s country-of-origin reputation influence perceived risk and trust, and then how those influences attitude towards electric vehicle adoption. Furthermore, the study investigates influence of attitude, along with subjective norms and facilitating conditions towards intention to adopt electric vehicles from China. A total of 260 valid responses from consumers living in major cities in Indonesia were collected. The PLS-SEM method was used to analyze the data. It was found that Hypotheses 7 was rejected due to no significant effect, while other hypotheses were accepted and have significant effect. Facilitating conditions did not influence electric vehicle adoption intention in this study because most of the respondents came from high-income groups and were able to facilitate themselves with home charging devices. This result can be used as insight for government or car manufacturers to create suitable facilitating conditions that can improve adoption intention of Chinese electric vehicle in Indonesia for consumers who are unable to facilitate themselves.